Civic and Ethnic Nationalism in Nepal: Distinct Features or Intertwined Essentials? - Pandey, Sushil Chandra (Literary Studies, 2024)
This research paper attempts to explore the complex dynamics of civic and ethnic nationalism in Nepal, assessing whether these two aspects of nationalism contrast or intertwine against the backdrop of the country's diversity and plurality. This study provides a comprehensive critical appraisal of the literature regarding nationalism in Nepal, analyzing the dichotomy between civic nationalism and ethnic nationalism. It attempts to explore the historical, cultural, and political factors that contribute to molding the discourse of nationalism in Nepal, shedding light on the tensions and implications of these two contrasting forms of nationalism. This study examines how civic and ethnic nationalism has evolved, influenced, interacted, and contrasted with the diverse socio-political landscape of Nepal. The debate on the historical roots of civic and ethnic nationalism can be traced back to the "integration" campaign of King Prithvi Narayan Shah in the 18th century. On the one hand, Shah's campaign was interpreted as a great work of "national integration,” on the other hand, it was termed as an act of expansionism and internal colonialism. Against this backdrop, the discourse of Nepali nationalism has evolved so far. Moreover, the historical roots of ethnic nationalism in Nepal can be traced to the assertion of ethnic identities and demands for cultural recognition. This study, through a comprehensive analysis of historical, theoretical, and empirical contexts, with a qualitative approach, attempts to unveil the complex dynamics between two aspects of nationalism. On the one hand, civic nationalism claims to emphasize shared values and collective representation whereas ethnic nationalism focuses on distinct cultures and identities blaming each other for leading the country to secession or trying to continue the historical discrimination in the name of unity. Amidst this, this research illuminates the different trajectories of Nepali nationalism discourse for social cohesion, state-building, and unity in diversity.